Pembuatan Kompos dan Aplikasinya Pada Budidaya Tanaman Padi Organik di Desa Girimukti - Ibrahim Danuwikarsa; Rubi Robana (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2016)
To support organic farming program, it has done community service program in the village Girimukti, Saguling sub-district, West Bandung regency, in the form of agricultural extension and practice of composting rice straw and water hyacinth.The program uses methods of PTD (Participatory Technology Development). Through this program, representatives of farmer group members have acquired skills composting. The application of compost with a basis of water hyacinth biomass using bio-activators MOL banana weevil, dry grain harvest produce as much as 8,572 kg / ha, and has increased interest by farmers to grow organic rice in the next planting season.